R-A-D-E-C: A LEARNING LANGUAGE PERSPECTIVE IN ELEMENTARY SCHOOL (International Conference on Elementary Education, 2018)
The goal of the study was to investigated how R-A-D-E-C step (Reading-Answer-Discuss-Explain-Create) by Sopandi integrated with language learning in Elementary Education. This study was qualitative descriptive research with observation and interview as an instrument. It explained the R-A-D-E-C Step and the four-language ability which are Listening, Reading, Speaking, and Writing. Based on this study, R-A-D-E-C learning model gives the children an opportunity to developed the language ability. R-A-D-E-C also optimize the function of the whole language learning approach in Elementary School.